Predictive models of ultimate and serviceability performances for underground twin caverns - Zhang, Wengang (2016)
The construction of a new cavern modifies the state of stresses and displacements in a zone around the existing cavern. For multiple caverns, the size of this influence zone depends on the ground type, the in situ stress, the cavern span and shape, the width of the pillar separating the caverns, and the excavation sequence. Performances of underground twin caverns can be unsatisfactory as a result of either instability (collapse) or excessive displacements. These two distinct failures should be prevented in design. This study simulated the ultimate and serviceability performances of underground twin rock caverns of various sizes and shapes. The global factor of safety is used as the criterion for determining the ultimate limit state and the calculated maximum displacement around the cavern opening is adopted as the serviceability limit state criterion. Based on the results of a series of numerical simulations, simple regression models were developed for estimating the global factor of safety and the maximum displacement, respectively. It was proposed that a proper pillar width can be determined based on the threshold influence factor value. In addition, design charts with regard to the selection of the pillar width for underground twin rock caverns under similar ground conditions were also developed.